Slope Stability Analysis of Pit X Using the Morgenstern-Price and Dump Slope Rating Methods - Ferdinan Rio; Budhi Setiawan; Rosihan Pebrianto (Jurnal Ilmiah Dinamika Rekayasa, 2025)
This study evaluates slope stability in Pit X, located in the open-pit mining area of PT Bukit Asam, Muara Enim Regency, South Sumatra. The site was previously used as a disposal area for overburden material, resulting in heterogeneous geotechnical characteristics and a higher potential for slope instability. The approaches applied in this study include the limit equilibrium method to calculate the factor of safety (FoS) and the Dump Slope Rating (DSR) method to assess the risk level of the slope empirically. The data were obtained from field observations and laboratory testing of shear strength parameters. The results show that section B–B’ had the lowest FoS of 1.61 and a DSR score of 63, classified as poorly stable, while section D–D’ had a FoS of 3.36 and a DSR score of 93, indicating very stable conditions. The consistency between both methods confirms that the integrated approach is practical in evaluating slope conditions and providing technical recommendations under complex geotechnical settings.